A Phase I Study of Dasatinib with Concurrent Chemoradiation for Stage III Non-Small Cell Lung Cancer - Safran, Howard; DiPetrillo, Thomas; Khurshid, Humera; Ng, Thomas; Mantripragada, Kalyan; Birnbaum, Ariel; Berz, David; Radie-Keane, Kathy; Perez, Kimberly; Constantinou, Maria; Luppe, Denise; Schumacher, Andrew; et al. (Frontiers in Oncology, 2012)
Objectives: Src family kinases (SFKs) are expressed in NSCLC and may be involved in tumor growth and metastases. Inhibition of SFK may also enhance radiation. The purpose of this study was to evaluate if a maximum dose of 100 mg of dasatinib could be safely administered with concurrent chemoradiation and then continued as maintenance for patients with newly diagnosed stage III NSCLC. Methods: Patients with stage III locally advanced NSCLC received paclitaxel, 50mg/m2/week, with carboplatin area under the curve (AUC) = 2, weekly for 7 weeks, and concurrent radiotherapy, 64.8 Gy. Three dose levels of dasatinib 50, 70 and 100mg/day were planned. Results: Eleven patients with locally advanced NSCLC were entered. At the 70 mg dose level 1 patient had grade 5 pneumonitis not responsive to therapy, and 1 patient had reversible grade 3 pneumonitis and grade 3 pericardial effusion. Due to these toxicities the Brown University Oncology Group Data Safety Monitoring Board terminated the study. Conclusion: Dasatinib could not be safely combined with concurrent chemoradiation for stage 3 lung cancer due to pneumonitis.